Use of endpoints in multiple myeloma randomized controlled trials over the last 15 years: A systematic review. Issue 6 (1st April 2021) - Mohyuddin, Ghulam Rehman; Koehn, Kelly; Abdallah, Al‐Ola; W. Sborov, Douglas; Rajkumar, S. Vincent; Kumar, Shaji; McClune, Brian
Abstract: Surrogate endpoints are being used more frequently in randomized controlled trials, even though they do not consistently corelate with patient outcomes. We systemically evaluated the use of surrogate endpoints in multiple myeloma randomized controlled trials over the past 15 years. We searched three databases (Pubmed, Embase, Cochrane) for multiple myeloma randomized controlled trials from January 1, 2005 to December 30, 2019. The primary outcome of our study was the proportion of randomized controlled trials that used overall survival as their primary endpoint. Secondary outcomes included the use of surrogate endpoints, and trends over time, and whether they differed based on study sponsorship. We included 151 randomized controlled trials in our analysis. The primary endpoint was overall survival (OS) in 17 (11.3%) of studies, progression free survival (PFS) or event‐defined endpoints in 91 studies (60.3%) and response‐based endpoints in 44 studies (29.1%). Quality of life was a primary endpoint in only three studies (2%). The use of OS as a primary endpoint decreased from 28.5% of trials from 2005 to 2009 to 5.5% from 2015 to 2019. There has been a decrease in the clinically meaningful endpoint of OS over the past 15 years in multiple myeloma randomized controlled trials. Use of quality of life as a primary endpoint remains exceedingly low. It remains paramount to recognize that the use of surrogate endpoints is imperfect, and care based upon them requires constant physician and patient re‐analysis.